PERANCANGAN SISTEM INFORMASI MANAJEMEN KEUANGAN DI AMIK GARUT - Tedi Budiman (INTERNAL (Information System Journal), 2020)
Financial information system is an information system that provides information to individuals or groups of people, both inside and outside the company that contains financial problems and information about the flow of money for users in the company. Financial information systems are used to solve financial problems in a company, by meeting three financial principles: fast, safe, and inexpensive.Quick principle, the intention is that financial information systems must be able to provide the required data on time and can meet the needs. The Safe Principle means that the financial information system must be prepared with consideration of internal controls so that company assets are maintained. The Principle of Inexpensive, the intention is that the cost of implementing a financial information system must be reduced so that it is relatively inexpensive.Therefore we need technology media that can solve financial problems, and produce financial information to related parties quickly, safely and cheaply. One example of developing information technology today is computer technology and internet. Starting from financial problems and technological advances, the authors make a website-based financial management application to facilitate the parties that perform financial management and supervision.Method of development application program is used Waterfall method, with the following stages: Software Requirement Analysis, Software Design, Program Code Making, Testing, Support, Maintenance.